The use of arthroscopy in diagnosing and treating sports-related cartilage lesions - Al Mamun, Abdullah; Al Muti, Abdullah; Monir, M. Moniruzzaman; Hannan, Abdul; Rahman, M. Mofizur (International Journal of Research in Orthopaedics, 2024)
Background: Sports-related cartilage lesions pose challenges for athletes. Cartilage, vital for smooth joint movement, can be damaged. Arthroscopy, a minimally invasive procedure, allows precise diagnosis and treatment of joint issues, offering quicker recovery and minimal scarring, enhancing orthopedic interventions. This study aimed to assess the use of arthroscopy in diagnosing and treating sports-related cartilage lesions. Methods: This prospective observational study was conducted at the department of orthopaedics and traumatology, Life Line Hospital Moulovibazar, Mount Adora Hospital Sylhet, MAG Osmani Medical College Hospital Sylhet, Bangladesh from January 2022 to December 2023. As the study subjects, a total of 58 patients with non-surgically treated acute or chronic sports-related cartilage lesions were enrolled by using a purposive sampling technique. After 6 months, a follow-up report was recorded. Data were analyzed by using Microsoft Office tools. Results: In this study, 72% of participants underwent cuff repair, with the remaining 28% opting for loop repair. The arthroscopic assessment revealed anterior medial cartilage lesions in 34% and anterior lateral lesions in 28%. Posterior medial, posterior lateral, and mid-talus dome cartilage lesions were observed in 17%, 5%, and 16%, respectively. Capsule repair was employed in 86% of cases. Significant improvement in hip range of motion, as well as radiological parameters like lateral center-edge angle, alpha angle (anteroposterior), and alpha angle (Dunn), was observed 6 months postoperatively (p<0.001). Conclusions: In detecting and treating sports-related cartilage lesions, arthroscopy is an effective method. This minimally invasive less painful treatment approach contributes to faster rehabilitation and a quicker return to normal activities.